Exploiting Heparan Sulfate Proteoglycans in Human Neurogenesis—Controlling Lineage Specification and Fate - Yu, Chieh; Griffiths, Lyn R.; Haupt, Larisa M. (Frontiers in Integrative Neuroscience, 2017)
Unspecialized, self-renewing stem cells have extraordinary application to regenerative medicine due to their multilineage differentiation potential. Stem cell therapies through replenishing damaged or lost cells in the injured area is an attractive treatment of brain trauma and neurodegenerative neurological disorders. Several stem cell types have neurogenic potential including neural stem cells (NSCs), embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs) and mesenchymal stem cells (MSCs). Currently, effective use of these cells is limited by our lack of understanding and ability to direct lineage commitment and differentiation of neural lineages. Heparan sulfate proteoglycans (HSPGs) are ubiquitous proteins within the stem cell microenvironment or niche and are found localized on the cell surface and in the extracellular matrix (ECM), where they interact with numerous signaling molecules. The glycosaminoglycan (GAG) chains carried by HSPGs are heterogeneous carbohydrates comprised of repeating disaccharides with specific sulfation patterns that govern ligand interactions to numerous factors including the fibroblast growth factors (FGFs) and wingless-type MMTV integration site family (Wnts). As such, HSPGs are plausible targets for guiding and controlling neural stem cell lineage fate. In this review, we provide an overview of HSPG family members syndecans and glypicans, and perlecan and their role in neurogenesis. We summarize the structural changes and subsequent functional implications of heparan sulfate as cells undergo neural lineage differentiation as well as outline the role of HSPG core protein expression throughout mammalian neural development and their function as cell receptors and co-receptors. Finally, we highlight suitable biomimetic approaches for exploiting the role of HSPGs in mammalian neurogenesis to control and tailor cell differentiation into specific lineages. An improved ability to control stem cell specific neural lineage fate and produce abundant cells of lineage specificity will further advance stem cell therapy for the development of improved repair of neurological disorders. We propose a deeper understanding of HSPG-mediated neurogenesis can potentially provide novel therapeutic targets of neurogenesis.